Problems and Management for Environmental Conditions in Human of the Islands of Istanbul - (:unkn) unknown (MARMARA UNIV, 2015)
Comparison of the increase in the population today, the concentration of human activities has led to the increased interaction of natural and human environment. Population growth, agriculture, industrialization, urbanization, constitute influence and pressure on the natural environment, many human factors such as transport and tourism. The relationship between the natural and human environment interaction unplanned, irregular, has led to the emergence of problems in many areas, especially in space. Today, the increase of the human environment related issues revealed management and sustainability of these problems. Detection of human -induced problems, providing management and sustainability, natural environment, space conservation, use and has become very important in terms of the future. The province of Istanbul, Istanbul Islands have a different structure in terms of geographic features, although the structure of protected natural environment is one of the areas that are experiencing human -induced problem. In this study, the detection of the human environment related issues in Istanbul Island occurring geographical perspectives and methods of analysis, evaluating their effect on space utilization and sustainability management were examined.
Keywords: Istanbul Island; land and problem management; sustainability; geographical analysis